1977
DOI: 10.1042/bj1670513f
|View full text |Cite
|
Sign up to set email alerts
|

Purification, biochemical characterization and serological analysis of cellular deoxyribonucleic acid polymerases and a reverse transcriptase from spleen of a patient with myelofibrotic syndrome

Abstract: The present study describes the separation and purification of a reverse transcriptase and cellular DNA polymerases from the human spleen of a patient with myelofibrotic syndrome. The specific requirements with respect to bivalent cations and template-primers for DNA polymerase-alpha, DNA polymerase-beta and DNA polymerase-gamma, as well as for the reverse transcriptase, are reported. Sedimentation-velocity measurements of the purified enzymes gave values of 150000, 40000, 100000 and 70000 daltons for DNA poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Aniong the most consistent findings has been the detection of an R T activity associated with a 70s RNA molecule (Baxt and Spiegelman, 1972) contained in a cytoplasmic particle with a density of 1.16 to 1.18 g/cm3 . In some cases, this D N A polymerase has been shown by immunological tests to be related to the R T of the SSV-I/GaLV group (Todaro and Gallo, 1973 Chandra and Steel, 1977).…”
Section: Discussionmentioning
confidence: 97%
“…Aniong the most consistent findings has been the detection of an R T activity associated with a 70s RNA molecule (Baxt and Spiegelman, 1972) contained in a cytoplasmic particle with a density of 1.16 to 1.18 g/cm3 . In some cases, this D N A polymerase has been shown by immunological tests to be related to the R T of the SSV-I/GaLV group (Todaro and Gallo, 1973 Chandra and Steel, 1977).…”
Section: Discussionmentioning
confidence: 97%
“…A metabolic workup was performed, including a complete blood count, serum and urine biochemistries, and vitamin D and parathyroid assays. Abnormalities noted were as follows (normal values in parentheses): hemoglobin 11.6 g/dl (12)(13)(14)(15)(16), hematocrit 35% (37-47), sedimentation rate (Westergren) 28 mm/h (0-20), urinary calcium excretion 20 mg per 24 h (SO-250), and urinary phosphorus excretion 575 mg per 24 h (900-1300). To accurately image the skull, a computed tomographic scan was performed ( Fig.…”
Section: Patientmentioning
confidence: 99%
“…RPMI-1640 and fetal calf serum were obtained from GIBCO (Glasgow, Scotland) and penicillin-streptomycin from Eurobio (Paris, France); gentamycin was from Flow Laboratories (McLean, VA), PHA-P was from DIFCO (Detroit, MI); recombinant IL-2 was from Genzyme Corporation (Boston, MA) and from Roussel-Uclaf (Romainville, France). Anti-interferon a was from Boehringer Mannheim (West Germany); labeled deoxythymidine triphosphate was from NEN-Chemical (Boston, MA); labeled deoxyguanosine triphosphate was from Amersham (Little Chalfont, Buckinghamshire, UK); nonlabeled deoxynucleoside triphosphate, oligodeoxyadenylic acid (dA,,), and template-primers poly(rA) (dT)1z-18, a RNA-DNA hybrid of a polyriboadenylic acid and oligodeoxythymidylic acid (chain length 12-18), poly(rC) ( c~G ) ,~-,~, a RNA-DNA hybrid of a polyribocytidylic acid and oligodeoxyguanylic acid (chain length [12][13][14][15][16][17][18], and poly(dA)*(dT), a DNA-DNA hybrid of polydeoxyadenylic acid and oligodeoxythymidylic acid (chain length 12-18), were from Pharmacia (Uppsala, Sweden). DEAE-cellulose (DE 52, microgranular) and phosphocellulose P (P11) were obtained from Whatman Biochemicals (Maidstone, Kent, UK).…”
Section: Reagentsmentioning
confidence: 99%
“…However, some RNA-dependent DNA polymerases exhibited the same elution profile as the muscle and melanoma enzymes. For example, the RNA-dependent DNA polymerase isolated from the spleen of a patient with myelofibrotic syndrome [37] and the RNA-dependent DNA polymerase of mouse sarcoma virus [38] did not bind to DEAE-cellulose. Recently we have found that the RNA-dependent DNA polymerase of human immunodeficiency virus type 2 was also not retained by DEAE-cellulose (Luke, unpublished results).…”
Section: Poly(c)p(dg) 12-18-monitored D N a Polymerase Activity In Mumentioning
confidence: 99%